Students’ Professional Self-Determination in the Context of the Socially Conditioned Conflicting Realities - E. F. Zeyer; M. V. Kormiltseva (Образование и наука)
The paper discusses the peculiarities of students’ professional identity in the context of socially conditioned conflicting realities. The individual social position is of a particular importance for the professional identity formation, so the authors carried out the research into the students professional self-determination with the reference to their socio-metric status in the academic group; the interpersonal relations were considered as conflict- generating – provoking the conflicting realities of students’ professional self- determination. The theoretical basis of the study involves the concept of personal professional growth with the emphasis on the students’ self-determination in the conflict situations. The research methodology combines the diagnostics of professional self-determination and socio-metric methods. The analysis and synthesis of the acquired empirical data reveal the differences in the expressed levels of components of the students’ professional identity according to their socio-metric status in the group. The research findings include the conformity of conflicting realities arising in interpersonal relationships in the academic process and reflected in the professional identity transformation. The above results can be used for psychological facilitation of students’ successful professional growth.